The rum diary - Robinson, Bruce, 1946-; Depp, Johnny; Eckhart, Aaron; Heard, Amber, 1986-; Thompson, Hunter S. (Culver City, Calif. : Sony Pictures Home Entertainment, 2012)
Freelance journalist Paul Kemp, writing for a run-down Puerto Rican newspaper, finds his work challenging amidst a dissolute group of expatriates and his obsession with the fiancée of a shady American real estate developer.
Based on the novel by Hunter S. Thompson.
Originally released as a motion picture in 2011.
Features: A voice made of ink and rage : inside "The rum diary," "The rum diary" back story.
Johnny Depp, Aaron Eckhart, Amber Heard, Michael Rispoli, Richard Jenkins, Giovanni Ribisi.
MPAA rating: R.
DVD, Dolby digital 5.1.
Keywords: Thompson, Hunter S. -- Film adaptations; Journalists -- Puerto Rico -- Drama; Real estate developers -- Corrupt practices -- Puerto Rico -- Drama; Rum -- Drama; San Juan (P.R.) -- Social life and customs -- Drama; Video recordings for the hearing impaired; Fiction films; Based on the book; Feature films; Comedy films